San Miguel : expanding the amaranth market - Elias, Jaan; Hernandez, Mario Alan Gonzalez; Garcia, Carlos Gil; Canales, Rodrigo; Khoshnood, Kaveh ([London] : SAGE, 2016)
Benito Manrique, his brother Diego, and Bruno Pagliai founded a small amaranth factory in the out-of-the-way Mexican village of Huixcazdha. Despite the plant's unschooled work force, the company had pioneered the processing of amaranth into a number of unique products. The company also had played a significant role in the development of the small community in which it was located. The company's primary customer had been the governments of Mexican states that used San Miguel's products in their dietary programs. Amaranth has many nutritional properties. It is gluten free and high in protein, containing essential amino acids not present in other vegetative food sources. In spite of these qualities, the amaranth market had never really taken off. This case study discusses this topic.
Originally Published in: Elias, J., Gonzalez Hernandez, M. A., Gil Garcia, C., Canales, R., & Khoshnood, K. (2014). San Miguel - Expanding the Amaranth Market. 101-14. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/amaranth.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Amaranth products -- Case studies; Marketing -- Case studies; Social entrepreneurship -- Case studies